Linear viscoelastic models from creep and complex modulus testing in soil-emulsion - Paulo Mateus Barros Rodrigues; Silvrano Adonias Dantas Neto; Lucas Feitosa de Albuquerque Lima Babadopulos; Jorge Luiz Oliveira Lucas Júnior (REM: International Engineering Journal)
Abstract This article describes the development and validation of a linear viscoelastic model 2S2P1D for silty sand mixed with 16% asphalt emulsion. Experimental data from creep tests were employed to propose and validate the model. The methodology involved soil collection and characterization, after which it was mixed with asphalt emulsion, and exposed to air for 24 hours, followed by the Superpave rotary compaction of the soil-emulsion mixture. Test samples were then exposed to air until a constant density loss was detected, followed by conducting complex modulus tests at thirty different temperature-frequency pairs. Based on these results and the smooth construction of the master curve of the mixture, it was confirmed that the material studied is thermorheologically simple, and the parameters of the linear 2S2P1D model were defined. After defining the constitutive model, a creep test was conducted on the material at a temperature of 0°C for 7200 seconds. The model exhibited satisfactory adjustments to the creep test results, even in the nonlinearity domain. The differences between the strains predicted by the model and those defined experimentally were considered within an acceptability limit for geotechnical materials, and the introduction of a modulus decrease coefficient of approximately 65% was sufficient to simulate the nonlinearity effect in the 2S2P1D model.